2021
DOI: 10.3390/molecules26092735
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide-Based Drug Delivery Systems for the Treatment of Periodontitis

Abstract: Periodontal diseases are worldwide health problems that negatively affect the lifestyle of many people. The long-term effect of the classical treatments, including the mechanical removal of bacterial plaque, is not effective enough, causing the scientific world to find other alternatives. Polymer–drug systems, which have different forms of presentation, chosen depending on the nature of the disease, the mode of administration, the type of polymer used, etc., have become very promising. Hydrogels, for example (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 105 publications
0
24
0
Order By: Relevance
“…10 Bilayer films can be made as mucoadhesive films by using mucoadhesive polymers with the added advantage of incorporating a sustained drug release layer 11 and an immediate drug release. 12 Various mucoadhesive films containing antimicrobial agents for the treatment of periodontitis have been reported; 3,[13][14][15] however, no significant efforts have been made in designing bi-layered mucoadhesive films for potential periodontitis treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Bilayer films can be made as mucoadhesive films by using mucoadhesive polymers with the added advantage of incorporating a sustained drug release layer 11 and an immediate drug release. 12 Various mucoadhesive films containing antimicrobial agents for the treatment of periodontitis have been reported; 3,[13][14][15] however, no significant efforts have been made in designing bi-layered mucoadhesive films for potential periodontitis treatment.…”
Section: Introductionmentioning
confidence: 99%
“… 2 The most prominent causative microorganisms are Porphyromonas gingivalis, Prevotella intermedia, Tannerella forsythia, Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum , and many others. 3 It has recently been established that Gram-negative and Gram-positive bacteria are associated with the progression of periodontal bone loss. 4 For the treatment of periodontal disease, various strategies have been developed including conventional procedures, scaling, and root planning; however these procedures are highly dependent upon clinician’s skill and have an inability to reach into deep pockets or furcation areas.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the large number of functional groups such as carboxyl and hydroxyl groups on the backbones of polysaccharide polymers allow flexible modifications of the hydrogel to complex with different drugs and later release them via various cues ( Cassimjee et al, 2020 ). It was reported that a polysaccharide-based wound dressing hydrogel was encapsulated with antimicrobial substance and wound repair substance such as anti-inflammatory drugs ( Baranov et al, 2021 ), proteolytic enzymes ( Auriemma et al, 2020 ), and growth factors ( Delair, 2012 ). Deng et al also reported a sodium alginate-based hydrogel embedded with semiconductor-like metal–organic frameworks encapsulating noble metal nanoparticles.…”
Section: Design Considerationsmentioning
confidence: 99%
“…These hydrogels also exhibited anti-inflammatory activity by reducing reactive oxygen species formation and modulating cytokine production in gingival fibroblasts [ 131 ]. Nanoparticles can be used to support polymer-drug conjugates such as polysaccharides to maintain a constant high concentration of the drug in a periodontal pocket [ 132 ].…”
Section: Nanoparticlesmentioning
confidence: 99%